Depositional processes and stratigraphic evolution of the Campanian deltaic system of la Anita Formation, Austral-Magallanes Basin, Patagonia, Argentina. (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Coastal depositional systems are commonly classified in terms of the relative interaction of wave, tide and fluvial processes. The La Anita Formation represents the opportunity to study and better understand coastal sedimentary systems. It is a poorly studied prograding siliciclastic deltaic-coastal wedge accumulated in the Campanian during the foreland stage of the Austral-Magallanes Basin. A detailed depositional process-based facies analysis have allowed the definition of 13 sedimentary facies and 9 facies associations for the La Anita Formation, ranging from prodelta to interdistributary delta-channel deposits. According to the spatial distribution of these facies associations, the La Anita Formation was divided into two informal units bounded by a regional erosion surface. The lower unit shows abundant hummocky cross-bedded and bioturbated sandstones, coarsening-upward trends and mainly aggradational to progradational vertical stacking pattern, and it was interpreted as a wave-dominated fluvial-influenced delta. The upper unit is characterized by unidirectional dune cross-bedding, coarsening-upward trend and a progradational vertical stacking pattern, and was interpreted as a fluvio-dominated delta with no evidence of tide or wave influence. These two units represent two genetically unrelated depositional sequences bounded by a regional erosion surface, which is interpreted as a sequence boundary triggered by a relative sea-level fall. The lower unit is part of a progradational highstand systems tract which involves the underlying deep-marine Alta Vista Formation. The upper unit deposits reflect a complete relative sea-level cycle which includes an undifferentiated lowstand and transgressive systems tracts and, toward the top, highstand systems tract.